ПОРІВНЯЛЬНИЙ АНАЛІЗ МАГНІТНИХ СИСТЕМ ЕЛЕКТРОДВИГУНІВ З ПОСТІЙНИМИ МАГНІТАМИ ДЛЯ ТРАМВАЯ - Гребєніков, В.В.; Гамалія, Р.В.; Дадичін, С.А. (Інститут електродинаміки НАН України, Київ, 2021)
A numerical study of eight configurations of magnetic systems of electric motors with permanent magnets for driving a tram was carried out. The permanent magnet electric motor can be used as a high-speed electric drive to replace the existing DC electric drive of a tram, and as a low-speed gearless electric drive of a new generation tram. The most promising configurations of magnetic systems of electric motors with permanent magnets for tram drive have been determined. By varying the geometrical and winding parameters of each of the investigated models of electric motors, the mechanical characteristics are determined, at which the given torque and power are achieved in the entire range of the rotor speed. Also, a thermal calculation was performed taking into account the urban driving cycle of high-speed electric motors with air cooling by a fan and low-speed ones in liquid cooling mode. The calculation of the characteristics of the investigated electric motors was carried out in the Simcentre MotorSolve software package. References 13, figures 8, tables 3.